E-government and the Transformation of Public Administration in Developing Countries: A Case Study of the Kenya Revenue Authority - Kerandi, Andrew Maranga (Université d'Ottawa / University of Ottawa, 2015)
One question that continues to occupy the minds of scholars of e-government is whether information and communication technologies (ICT) can transform public administration. General opinion on the subject is sharply divided: some believe that e-government can shape public administration, while others doubt that it can have this effect. At the empirical level, the testing of the influence of e-government on public administration has been largely ignored. Consequently, the fundamental question remains unanswered, as do the further questions of precisely how and with what effects might information and communication technologies be reshaping public administration. These are the questions that motivated the research presented here, which examines and describes the transformative powers of e-government by focusing on the use of information and communication technologies to transform a particular public agency, the Kenya Revenue Authority. The research used two main methods of data collection and construction: interviewing senior management at the Kenya Revenue Authority (KRA) and reviewing documents obtained from the KRA and other public sources. A transformation change analytical framework was used to analyze the KRA before the implementation of ICT-enabled reforms as an organization needing change and after these reforms as a transformed organization. The results of the findings suggest that, although ICT has had some beneficial effects on the KRA, the changes produced to date fall short of being described as transformative. While the KRA has experienced significant improvements in performance in terms of revenue, it has yet to fully integrate its operations, change its organizational structure to achieve optimal efficiency, or transform the organizational behaviour and culture of its staff in ways that improve its operations or enhance its public image.
Keywords: E-Government; Public Administration; Transformation